Study Of Self-Employment Intention Of Students Majoring In Entrepreneurship In Malaysian Universities - Hj Zainuddin, Muhammad Nizam (2009)
This research attempts to comfirm self-employment intentions from both internal and external antecedents by building on Ajzen\'s (1991) Theory of Planned Behaviour model.